National hydrogen strategy: Clear focus and consistent implementation necessary - Martin Kittel; Dana Kirchem; Wolf-Peter Schill; Claudia Kemfert (DIW Weekly Report, 2023)
Replacing fossil fuels with renewable energy sources is one cornerstone of the energy transition. In certain sectors, green hydrogen will play an important role in the future, as is envisioned in the revised National Hydrogen Strategy recently presented by the German Federal Government. This Weekly Report discusses important changes in this strategy compared to the first National Hydrogen Strategy from 2020. It focuses on the analysis of the hydrogen quantities planned for 2030, which can likely only be realized with significant effort. In addition, it is uncertain how large the remaining share of non-green hydrogen would be. Green hydrogen imports are of particular significance and must be secured early on. It is now important to implement the strategy in a timely and consistent fashion. In this context, focus should remain on the areas of application that are required from an energy system perspective and for which direct electrification, which is more energy efficient, is not possible, especially in industry as well as aviation and shipping.
Keywords: Q41; Q48; 330; hydrogen; electrolysis; imports